Potential Correlation Between Eczema and Hematological Malignancies Risk: A Systematic Review and Meta-Analysis - Liang, Zuohui; Liu, Jie; Jin, Hongxia; Teng, Yirong; Xu, Shuangyan; Yan, Weimin; Zhu, Yun (Frontiers in Medicine, 2022)
Background: Eczema characterized by itch, sleeplessness, and adverse effects on quality of life is associated with a risk of hematological malignancies. However, there is a controversy pertaining to whether this association implies a greater or lesser risk of hematological cancers. We aimed to explore the link between eczema and hematological malignancies risk. Methods: We systematically searched PubMed and Embase databases from their inception to February 17, 2022. Two reviewers independently screened articles, extracted data and assessed study quality, respectively. The odds ratios and 95% confidence intervals (CIs) were pooled by using fixed or random-effects models. Results: 29 studies involving 2,521,574 participants examined the contribution of eczema to hematological malignancies. We found that eczema significantly increased the risk of Hodgkin’s lymphoma (1.44; 95% CI, 1.07–1.95), myeloma (1.15; 95% CI, 1.04–1.28), and significantly decreased the risk of lymphocytic leukemia (0.91; 95% CI, 0.84–0.99); however, it is not significantly associated with Non-Hodgkin’s lymphoma, and myelocytic leukemia. Conclusion: Eczema has been shown to be associated with the risk of hematological cancer, this association still needs to be verified in large randomized controlled trials.